1976
DOI: 10.3168/jds.s0022-0302(76)84355-x
|View full text |Cite
|
Sign up to set email alerts
|

Diet Calcium and pH Versus Mineral Balance in Holstein Cows 84 Days Pre- to 2 Days Postpartum

Abstract: Sixteen dry Holstein cows were assigned four groups combining either .2 or 2.1% calcium and pH of either 4.5 or 6.1 in a 2 X 2 factorial arrangement of treatments to study the effect of diet calcium and acidity (pH) on voluntary intake of dry matter, mineral metabolism, and blood constituents. The 86-day experiment was started 84 days prepartum and completed 2 days postpartum. Voluntary dry matter ingestion tended to be higher with higher calcium and acidity (lower pH) diets. Calcium nutriture was improved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Greater Ca urinary excretion and lower pH in the groups supplemented with anionic salts demonstrated that there is a significant effect of these salts on the kidney. Block (1984) hypothesized that at least part of (Verdaris and Evans, 1976;Horst, 1986;Fredeen et al, 1988;Horst et al, 1994). The animals of SA and GA in this study did not have significantly greater VITD concentrations, despite the level observed for group GA on d 3.…”
Section: Discussionmentioning
confidence: 50%
“…Greater Ca urinary excretion and lower pH in the groups supplemented with anionic salts demonstrated that there is a significant effect of these salts on the kidney. Block (1984) hypothesized that at least part of (Verdaris and Evans, 1976;Horst, 1986;Fredeen et al, 1988;Horst et al, 1994). The animals of SA and GA in this study did not have significantly greater VITD concentrations, despite the level observed for group GA on d 3.…”
Section: Discussionmentioning
confidence: 50%
“…Higher concentration of plasma Mg were observed when cows were fed a prepartum diet low in Ca compared to a prepartum diet high in Ca (Verdaris and Evans 1975). It is now evident that prepartum diets low in Ca enhance bone resorption during the periparturient period to maintain plasma Ca concentration (Green et al 1981; Kichura et al 1982).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism by which the acidotic stage affects calcium metabolism and homeostasis is not fully understood, but it is suggested that the effect is mediated via an enhancement of the stimulatory effects of PTH [52]. Increased plasma hydroxyproline concentration suggests that bone resorption may be involved [67], and some studies reported an increase in the apparent calcium absorption from the digestive tract [113,69], while others found no changes [106], or even a decrease [67]. The extensive urinary calcium excretion seen in cows fed anionic salts, may stimulate the vitamin D-related calcium homeostatic mechanisms, and in this way help prevent parturient paresis [111].…”
Section: Acidifying Rations (Dietary Cation-anion Difference Dcad)mentioning
confidence: 99%